Interplay between nutrition, microbiota, and immunity in rotavirus infection: insights from human and animal models - Huo, Wenying; Qiao, Yingying; Li, Enkai; Li, Mengyun; Che, Long (Frontiers in Veterinary Science, 2025)
Rotavirus (RV) remains a leading cause of severe gastroenteritis in infants and young animals worldwide, contributing to significant morbidity and mortality despite the availability of vaccines. The gastrointestinal tract’s health, shaped by complex interactions between nutrition, the gut microbiota, and the host immune system, plays a crucial role in RV pathogenesis and outcomes. Emerging evidence suggests that dietary components not only influence the composition and function of the gut microbiota but also modulate immune responses essential for protection against RV. This review integrates findings from human and animal models to elucidate the interplay between nutrition, microbiota, and immunity in the context of RV infection. We aim to shed light on the mechanisms by which dietary factors and microbial communities influence RV susceptibility and severity, and how this knowledge could guide the development of more effective preventive and therapeutic strategies.